Peningkatan Pemahaman Masyarakat Terhadap Penegakan Hukum Lingkungan di Kelurahan Lembah Sari Kecamatan Rumbai PesisirKota Pekanbaru: ncreasing Public Understanding of Environmental Law Enforcement in Lembah Sari Village, Rumbai Pesisir District, Pekanbaru City - Olivia Anggie Johar; Yusuf Daeng; Tri Novita Sari M (CONSEN: Indonesian Journal of Community Services and Engagement, 2021)
Enforcement of Environmental Law consists of Enforcement of Environmental Administrative Law, Enforcement of Civil Environmental Law, and Enforcement of Criminal Environmental Law in accordance with Law No. 32 of 2009 concerning Environmental Protection and Management. Law Enforcement Environmental Administration requests that those who reject the law or not meet the requirements, stop or approve the original situation (before there is a conflict). Enforcement of Civil Environmental Law is the second law enforcement effort after administrative law because it only focuses on efforts to compensate victims for environmental pollution or damage. Criminal Law Enforcement receives an ultimum remedium or final legal remedy because law enforcement here is intended to cancel a security court or a fine for those who try to pollute and / or destroy the environment. Introductory discussion with dialogue, with work procedures to support the methods offered are lectures / discussions and dialogues conducted according to the schedule requested in accordance with partner requests for improvement in the discussion of program time. In this service program, it will produce scientific articles in accordance with the proposed activity plan, while for partners is knowledge about partners is knowledge about environmental law enforcement for the community of Lembah Sari.